Evaluation of a novel halophilic lipase secrection by marinobacter litoratis SW-45 for butyl esters synthesis from palm - based oils - Haliru Musa (School of Bioprocess Engineering, 2017)
The research focus on the following this study uses Malaysian crude palm oil (CPO) and crude palm kernel oil (CPKO) as feedstock, which was initially hydrolysed to free fatty acids (FFAs) and subsequent esterification using crude halophilic lipase; isolation, screening and identification of halophilic lipase-secreting microorganisms from various saline environments; this work only deal with crude halophilic lipase and the application of the crude lipase in characterization, compatibility and esterification studies; commercial lipase of Thermomyces lanuginosus was used as biocatalyst for hydrolysis of CPO and CPKO to corresponding FFAs, while crude halophilic lipase of Marinobacter litoralis SW-45 catalysed esterification of the FFAs to corresponding esters; this research is limited to esterification of hydrolysed FFAs by crude halophilic lipase and analysis of the synthesised esters was performed using only Gas Chromatographic (GC) technique.